Post Project Sustainability of watershed programme : a continuing challenge - B. Renuka Rani; K. Sai Maheswari (Journal of Agricultural Extension Management, 2025)
The watershed approach has aimed at treating degraded lands with the help of low cost and locally accessed technologies through a participatory approach that seeks to secure the close involvement of the user-communities. The concept of participatory watershed management emphasizes a multi-disciplinary and multi-institutional approach. The process begins with the management of soil and water, which eventually leads to the development of other resources. Human resource development and large scale participation is essential since finally it is the people who have to manage their resources.